Nomenclatural standards of apple cultivars developed at Sverdlovsk Horticultural Breeding Station. Part I - A. V. Shlyavas; D. D. Telezhinskiy; L. V. Bagmet (Труды по прикладной ботанике, генетике и селекции)
Researchers of the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) and Sverdlovsk Horticultural Breeding Station developed nomenclatural standards for 18 apple cultivars released at the said station: ‘Aksyona’ (WIR-53949), ‘Blagaya Vest’ (WIR-53950), ‘Danila’ (WIR-53952), ‘Isetskoye Pozdneye’ (WIR-53953), ‘Iset Belaya’ (WIR-53954), ‘Krasa Sverdlovska’ (WIR-53955), ‘Papiroyantarnoye’ (WIR-53956), ‘Pervouralskaya’ (WIR-53957), ‘Rodnikovaya’ (WIR-53958), ‘Rumyanka Sverdlovskaya’ (WIR-53959), ‘Sverdlovchanin’ (WIR-53960), ‘Serebryanoye Kopyttse’ (WIR-53961), ‘Sokovoye 3’ (WIR-53962), ‘Tavatuy’ (WIR-53963), ‘Uralets’ (WIR-53964), ‘Fakel’ (WIR-53965), ‘Fermer’ (WIR-53966), and ‘Ekrannoye’ (WIR-53967). Nomenclatural standards serve to confirm the authenticity of a cultivar and its name. They should be kept perpetually in the scientific herbarium collection. Herbarium specimens of nomenclatural standards are formatted in accordance with the recommendations of the International Code of Nomenclature for Cultivated Plants (ICNCP), registered in the VIR Herbarium Database and included in the Herbarium of Cultivated Plants of the World, Their Wild Relatives, and Weeds (WIR).